Incentives for Teacher Relocation: Evidence from the Gambian Hardship Allowance - Todd Pugatch; Elizabeth Schroeder (Institute for the Study of Labor (IZA), 2013)
We evaluate the impact of the Gambian hardship allowance, which provides a salary premium of 30-40% to primary school teachers in remote locations, on the distribution and characteristics of teachers across schools. A geographic discontinuity in the policy's implementation and the presence of common pre-treatment trends between hardship and non-hardship schools provide sources of identifying variation. We find that the hardship allowance increased the share of qualified (certified) teachers by 10 percentage points. The policy also reduced the pupil-qualified teacher ratio by 27, or 61% of the mean, in recipient schools close to the distance threshold. Further analysis suggests that these gains were not merely the result of teachers switching from non-hardship to hardship schools. With similar policies in place in more than two dozen other developing countries, our study provides an important piece of evidence on their effectiveness.
Keywords: I25; I28; J38; J45; J61; O12; O15; 330; teacher labor markets; rural schools; Gambia; program evaluation; regression discontinuity